Nyonya culture expression in Malaysian Chinese media based on Facebook - Wang, Xiaoyan; Syed Zainudin, Sharifah Sofiah; Yaakup, Hani Salwah (Redfame Publishing Inc., 2024)
In the digital age, the Malaysian Chinese media has become an important communication platform for Malaysian Chinese and has a key influence on cultural communication. Nyonya culture, a unique product of the fusion of Chinese and Southeast Asian cultures, has gained widespread attention and use in the media. In this research, 19 Facebook posts were coded and analyzed to investigate Nyonya culture as a comprehensive cultural symbol, its transmission of traditional Chinese culture in the five dimensions of food, crafts, traditional customs, social affairs, and media entertainment, as well as the integration of new cultural symbols. The study aims to provide a new approach to integrating and disseminating Nyonya culture in the context of digitalization, as wellas providing a unique perspective on the dissemination of traditional culture through Malaysian Chinese media.